The Universal Patient Centeredness Questionnaire: reliability and validity of a one-page questionnaire following surveys in three patient populations - Bjertnaes, Oyvind (Patient Relat Outcome Meas, 2016)
BACKGROUND: This study developed and tested the reliability and validity of the Universal Patient Centeredness Questionnaire (UPC-Q). METHODS: The UPC-Q developed in this study has three parts: 1) the aspects that patients consider the most important when receiving a relevant health care service, rating the health care services on these aspects and their prioritization, 2) the overall experiences of patients using the relevant health care service, and 3) suggestions for improvements. The UPC-Q was tested in four different patient-experience surveys in 2015, including psychiatric inpatients (n=109), general practitioner (GP) patients (n=1,059), and inpatients from two hospital samples (n=973, n=599). The UPC-Q was tested for item completeness and ceiling effects, while the UPC-Q scale consisting of the first part of the UPC-Q was tested for internal consistency reliability and construct validity. RESULTS: The percentage of patients rating at least one aspect was 70.6% for psychiatric inpatients, 77.6% for hospital inpatients, and 90.6% for GP patients, while 88.9% of the psychiatric inpatients, 93.1% of the hospital inpatients, and 95.3% of the GP patients were able to prioritize the aspects. The internal consistency reliability of the UPC-Q scale was acceptable in all samples (Cronbach’s alpha >0.7), and construct validity was supported by 20 of 21 significant associations between the UPC-Q and related variables. The UPC-Q total score was skewed toward positive evaluations, but the ceiling effect was smaller for an unbalanced response scale than for a balanced scale. CONCLUSION: The UPC-Q includes ratings of what is most important for individual patients, while at the same time providing data for improving the quality of health care and making it possible to monitor trends within and across patient populations. This study included psychiatric inpatients, hospital inpatients, and GP patients, and found that the UPC-Q performed well in terms of acceptance, internal consistency reliability, and construct validity.